Analisis Kesantunan Berbahasa pada Laporan Wawancara yang Ditulis Siswa Kelas VIII di SMP Negeri 1 Teras - Maria, Ana, Prof. Dr. Markhamah, M.Hum (2016)
The use of polite language in everyday life is an important role in communicating, because by using polite language that we can establish good relationships with others. The purpose of this study is to describe the analysis of politeness on interview reports written by the students of class VIII SMP Negeri 1 Terrace and explain the cause ketidaksantunan report written wawancarayang eighth grade students at SMP Negeri 1 terrace. Data collection techniques in this study using the analysis of politeness assignment techniques, engineering documentation and refer to. Based on the data that has been analyzed, found the task of students who apply and violate the principles of politeness and cause ketidaksantunan. Found six application of politeness principle, namely the application of the maxim of 11.4% wisdom, generosity maxim application of 20%, 37.1% appreciation maxim application, the application of the maxim of simplicity 5.7%, 17.1% consensus maxim application, Application Maksim kesimpatian 8, 6%. It was also found six deviations politeness principle, ie 3.2% deviation maxim of wisdom, generosity maxim deviation of 18.7%, 46.8% deviation award maxims, maxims simplicity deviation of 6.2%, 9.3% deviation consensus maxims, maxims deviation kesimpatian 18.7%. Found 4 ketidaksantunan cause, namely direct criticism with words of roughly 9%, boost a sense of emotion speakers 60.6%, deliberately accused opponents said 3%, deliberately discredit hearer 27.2%.